Production of Antibiotics from Endophyte Fungi Isolates of Bidara Plants (Ziziphus mauritina L.) Isolates Codes IFAZ-6, IFBZ-6, IFDZ-8 With Variations in Carbon Sources - Fitriana, Fitriana; Nurung, Ayyub Harly; Adnan, Afdina Putri (Journal Microbiology Science, 2024)
Research has been carried out on antibiotic production from endophytic fungal isolates coded IFAZ-6, IFBZ-6, and IFDZ-8 from bidara plants (Ziziphus mauritina L.) with variations in carbon sources. This research aims to determine antibiotic production with variations in carbon sources. The first stage was the purification of each selected endophytic fungal isolate. The endophytic fungal isolate was inoculated into the fermentation medium using a variety of carbon sources, namely glucose, fructose, and galactose for 21 days. The antibiotic activity was carried out using the agar diffusion method against Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli bacteria. The results obtained showed that the glucose carbon source was better in producing antibiotic compounds than the galactose carbon source in endophytic fungal isolates coded IFAZ-6, the glucose carbon source was better in producing antibiotic compounds than the fructose and galactose sources in endophytic fungal isolates coded IFBZ-6, and the fructose carbon source is better at producing antibiotic compounds than the galactose source in endophytic fungal isolates coded IFDZ-8.